Tafsir Atas Melawan Sifat Materil Yang Dilakukan Oleh Pejabat Administrasi Negara Dalam Kaitan Dengan Tindak Pidana Korupsi - Erdianto Efendi (Al-Risalah, 2011)
This writing concerns on Material‐Law contracharacter in putting corruptors in court in Indonesia. In the Bill number 20 year 2001 referring to Bill number 31 year 1999, it has been elaborated the position of law contradiction. Yet, that definition is lack of clarity that results in violation of the law,especially to the claimant (prosecutor). Real fact on the application of that Bill shows that there is uncertainty in the law enforcement of corruption. Therefore, the subjectivity of interpreting materiallaw contra‐character contradicts with the legal aspect of Indonesian crimanal‐law ally result in the violation of people human rights.